Le costituzioni di Gerardo da Sesso: gli statuti sinodali novaresi e i decreti emanati in qualità di legato apostolico - Olivieri, Antonio (Scrineum, 2013)
Gerard from Sesso was an important Lombard prelate close to pope Innocent III: at the end of his life (+ 1211 december) besides a Papal legate, he was elected bishop of Novara, designated cardinal bishop of Albano and, according to a poorly documented tradition, he was appointed archbishop of Milan for few months. Some scholars of 17-18th century ascribe to him a series of synodal decrees for Novara’s diocese and a body of disciplinary regulations that was spread among the clergy of Milan. The paper here proposed re-examines the documentation relating to these two collection of rules through a study of their structure and of their mutual relations based on Medieval specimens which are still unpublished or not well known to the scholars. We’ll also try to emphasize their complex stratification and correct some mistaken identities (for instance the attribution to Gerard of a group of legateship precepts which were on the contrary issued by cardinal Geoffrey from Castiglione in 1229).